The effects of minimum wage on wage distribution in urban China: Evidence from the CHIP data - Ma Xinxin; Shi Li (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
Using data from the China Household Income Project, this study analyzes the effects of minimum wage policy on wage distribution in urban China from 1993 to 2013. Several major conclusions emerge from this research. First, with respect to the effects of the minimum wage on wages for low-wage groups: 1.) The results of the ordinary least squares (OLS) and quantile regression (QR) models show that the minimum wage affected both the average wage and the wage levels for low-wage groups during 1993-1995, 1998-2002, and 2007-2013, with the greatest effect during 1993-1995; 2.) The results using the Neumark, Schweitzer, and Wascher (2004) model indicate that the change in the minimum wage level affected changes in the wage level for low-wage groups during 1993-1995 and 1998-2002, with the greatest effect during 1993-1995; 3.) The results of the DID model indicate that even when heterogeneity problems are addressed, the minimum wage considerably affects the wage levels for low-wage groups during all three periods. Second, all estimation results indicate the presence of a spillover effect in 1993-1995, but not in 1998-2002 or 2007-2013.
Keywords: J31; J33; J38; 330; minimum wage policy; wage distribution; urban China